Influence of Price Perception, Word Of Mouth, and Brand Trust On The Purchase Decision Of Juragan 99 Bus Tickets - Sinollah, Sinollah; Budi Wahono; Agung Winarno; Heri Pratikto (International Journal of Economics, Business and Innovation Research, 2024)
The land transport sector in Indonesia, particularly bus services like Juragan 99, encounters difficulties in acquiring and retaining clientele due to intense rivalry. This study seeks to examine the influence of pricing, word of mouth (WOM), and brand trust on the purchasing decisions for Juragan 99 bus tickets. The employed methodology is a quantitative survey, utilising data gathered from 200 respondents who utilise the Juragan 99 bus route. The findings indicated that price, word-of-mouth, and brand trust significantly affect purchasing decisions, both individually and collectively. The findings underscore the significance of marketing strategies that incorporate competitive pricing, efficient word-of-mouth management, and the establishment of brand trust through great service. This study offers significant insights for Juragan 99 management to enhance competitiveness in the Indonesian land transport sector